Analisis Pengaruh Prasyarat Kredit (5C) Terhadap Kelancaran Pembayaran Angsuran Nasabah Di Bank Kalsel Unit Sentra Antasari Banjarmasin - Shendy Apriana; Dwi Wahyu Artiningsih; Irwansyah Irwansyah (JURNAL BISNIS DAN PEMBANGUNAN, 2017)
The purpose of this study to prove the influence Prerequisite Credit (5C) partially composed of Character (X1), Capacity (X2), Capital (X3), Collateral (X4), Condition of Economy (X5) against Smoothness Payments (Y) Installment Customers Bank Kalsel Unit Sentra Antasari Banjarmasin, proving the influence Prerequisites Credits (Character, Capacity, Capital, Collateral, Conditions of Economy) simultaneously on the smoothness of Payments (Y) Installment of Customer in Bank Kalsel Unit Sentra Antasari Banjarmasin and prove variable (Character, Capacity, Capital, Collateral, Conditions of Economy) in which the most significant effect on the Payment Smoothness (Y) Installment of Customer in Bank Unit Sentra Antasari Banjarmasin in South Kalimantan.The study population is the Customer in Bank Unit Sentra Antasari Banjarmasin in South Kalimantan which amounts to 130 people. Sampling technique used sampling saturated. Collecting data using questionnaires designed using level Likert scale 1-5. Data analysis using SPSS structural model.The test results prove 1). Character (X1) partially significant effect on the smoothness of Payments (Y) Installment of Customer in Bank Unit Sentra Antasari Banjarmasin South Kalimantan with great influence 25.3%. 2). Capacity (X2) significant effect partially to the smoothness of Payments (Y) Installment of Customer in Bank Unit Sentra Antasari Banjarmasin in South Kalimantan to PT Bank Kalsel employee performance with great influence 26.7%. 3). Capital (X3) but not significant effect partially on Smoothness Payments (Y) Installment of Customer in Bank Unit Sentra Antasari Banjarmasin in South Kalimantan (1.1%). 4). Collateral (X4) significant effect partially to the smoothness of Payments (Y) Installment of Customer in Bank Unit Sentra Antasari Banjarmasin in South Kalimantan against the influence of 27.5%. 5). Condition of Economy (X5) but not significant effect partially on Smoothness Payments (Y) Installment of Customer in Bank Unit Sentra Antasari Banjarmasin in South Kalimantan (0.7%). 6). Prerequisites Credit (5C) but not significant effect simultaneously on the smoothness of Payments (Y) Installment of Customer in Bank Unit Sentra Antasari Banjarmasin in South Kalimantan (18.5%) of employees of PT Bank Kalsel performance with great influence 26.7% Training significant effect on Employee Performance PT Bank Kalsel with great influence 24.34% 3) Financial Compensation significant effect on employee performance PT Bank Kalsel with great influence 31.11%. The most dominant variable is a variable Collateral (X4) to the smoothness of the Customer Installment Payment Bank Unit Sentra Antasari Banjarmasin in South Kalimantan. Keywords: Prerequisites Credit, Character, Capacity, Capital, Collateral, Conditions of Economy, Smoothness Payments.